Knowledge, attitudes, beliefs and practices of Occupational Physicians towards seasonal influenza vaccination: a cross-sectional study from North-Eastern Italy - Riccò, M. (J Prev Med Hyg, 2017)
INTRODUCTION. The present study aims to characterize personal attitudes and knowledge of a sample of Italian Occupational Physicians (OPh) towards Seasonal Influenza Vaccine (SIV) in healthcare workers (HCWs). METHODS. In total, 92 OPh (42.4% males, 57.6% females, mean age of 47.3 ± 10.4 years, 50 specialists in Occupational Medicine, 42 specialists in Hygiene and Public Health) were asked about their attitudes towards influenza vaccine, their general knowledge of vaccine practice, their propensity towards vaccines and, eventually, their risk perception about the influenza and influenza vaccine was investigated. A regression analysis was then performed in order to better characterize predictive factors for vaccine propensity. RESULTS. Influenza was recognized as a vaccination recommended for HCWs in 89/92 of the sampled OPh (96.7%). However, prevalence of misconceptions about vaccines was relatively high, with 26/92 (28.3%) and 24/92 (26.1%) referring vaccinations as eliciting allergic and autoimmune diseases, respectively and identifying lethargic encephalitis (18/92, 19.6%), autism (17/92, 18.5%), diabetes mellitus (15/92, 16.3%) and multiple sclerosis (13/92, 14.1%) as causatively vaccine-related. Propensity towards influenza vaccination found a significant predictor in the general knowledge (beta coefficient 0.213, p value = 0.043), risk perception (beta coefficient 0.252, p value = 0.018) and general propensity towards vaccinations (beta coefficient 0.384, p value = 0.002). DISCUSSION. In spite of a diffuse propensity towards SIV, adherence of OPh was still < 50% of the sample. Moreover, sharing of misbeliefs and misconceptions was significant. As knowledge and risk perceptions were identified as significant predictors of vaccine propensity, our results suggest that information and training programs for OPh should be appropriately designed.